Analysis of Legal Regulations Relating to Menage, Pregnancy and Parenth Leave based on Positive Law in Indonesia - Saffa Abdullah Abdad; Alisa Zahra Sakdiya; Anissa Nur Zahrani; Nabila Ikbal; Safira Hafis Pradina; Tasya Cantik Alya Nabila (Universitas Muhammadiyah Surakarta, 2023)
The role of women is not only in the house but also has the opportunity to work just like a man. Women have a lot of potential both in terms of intellectual abilities and skills which then encourages a woman to enter the world of work. This research is a normative research method, namely legal research conducted by researching literature or secondary data which emphasizes the matter of statutory provisions related to menstruation and maternity leave. Based on the results of the research, arrangements regarding the right to leave for menstruation, pregnancy and childbirth are based on the positive law currently in effect in Indonesia. Leave is one of the solutions in women's performance in overcoming these problems. With the issuance of Law Number 13 of 2008 concerning the rights of women workers. Regarding the right to menstruation leave, female workers convey this to the company so that they are not required to work on the first and second day during menstruation. The right to maternity and maternity leave is regulated in Article 82 paragraph (1) of Law Number 13 of 2003 which states that female workers only get 1.5 (one and a half) months of rest before she gives birth and 1.5 (one and a half) months after she gives birth. the baby which must be based on calculations made by doctors and midwives. In this way, women workers receive protection for their own roles and health background, which men cannot have, such as menstruation, pregnancy, childbirth and breastfeeding babies.